Support theorem on stochastic flows with interaction - Pilipenko, A.Yu. (Інститут математики НАН України, 2006)
We prove an analogue of the Stroock–Varadhan theorem for stochastic ﬂows describing a motion of interacting particles in a random media. A version of the Itˆo lemma for functions on a measure-valued process is obtained.